Pengaruh Emoji Whatsapp: Analisis Penerimaan Pesan Komunikasi Remaja di Universitas Negeri Padang: Kajian Sosiolinguistik dalam Chat Whatsapp - Kintani, Aulia Ratu; Zahrina, Nisa Afra; Syahrul; Jamaluddin, Norliza Binti (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to digitally test the effects of emoji use in digital interactions among teenagers at Padang State University through the WhatsApp application. With a sociolinguistic, semiotic approach, this study examines and uses news submission, social relationship formation, and the formation of students' digital identities. This data was collected through in-depth interviews and content analysis of WhatsApp conversations. The results show that emojis not only play a role other than text, but also function as a means of emotional expression, which means confirmation, social status, and cultural symbolism of users. This study confirms the importance of emojis as an integral part of digital communication among young people. It is full of linguistic and cultural interests.